Brucella-infected abdominal aortic aneurysm: management strategies for an uncommon aneurysm - Ma, Huibo; Yang, Yuling; Liu, Huanhuan; Sun, Xiaozhi; Li, Yongxin; Guo, Mingjin (Frontiers in Medicine, 2023)
Objective The occurrence of Brucella-induced abdominal aortic aneurysms is an exceedingly rare phenomenon, yet it stands as one of the most severe complications within this context. The combined utilization of serological testing and imaging diagnostics has been validated as an effective approach for the identification of Brucella-induced abdominal aortic aneurysms. Presently, the predominant therapeutic strategies encompass antibiotic treatment and surgical intervention. Nonetheless, ongoing controversies persist concerning the establishment of diagnostic criteria, the optimal timing and selection of antibiotic regimens, and the nuanced decision between open surgical procedures and endovascular interventions. Through a meticulous analysis of cases originating from our institution as well as a comprehensive review of previously documented instances, we aim to engage in a detailed discourse on the salient diagnostic and therapeutic facets surrounding Brucella-induced abdominal aortic aneurysms. Methods We conducted a retrospective summary of three cases involving Brucella-induced abdominal aortic aneurysms treated within our institution. Furthermore, we performed a comprehensive PubMed search, without imposing restrictions on language or publication year, to identify pertinent literature pertaining to Brucella-induced abdominal aortic aneurysms. The selection criteria primarily focused on case reports delineating occurrences of abdominal aortic aneurysms attributed to Brucella infection. Results We present three distinct cases of Brucella-induced abdominal aortic aneurysms managed at our institution, providing comprehensive insights into the employed diagnostic and therapeutic approaches. Additionally, over the past five decades, a total of 24 cases in 23 publications of Brucella-induced abdominal aortic aneurysms have been reported on PubMed. The earliest report dates back to 1976. Conclusion Our analysis suggests that Brucella-induced abdominal aortic aneurysm is characterized by a remarkably low incidence but is associated with a substantial risk of life-threatening complications. The integration of serological and imaging assessments assumes pivotal importance in facilitating prompt diagnosis of this condition. The prompt initiation of targeted antibiotic therapy is recommended, and the selection of appropriate surgical strategies should be guided by considerations including aneurysm dimensions and morphological attributes. The timely identification and intervention carry utmost significance in retarding disease advancement and ameliorating unfavorable clinical outcomes.